Astrocyte senescence and SASP in neurodegeneration: tau joins the loop. Issue 8 (18th April 2021) - Ungerleider, Kyra; Beck, Jessica; Lissa, Delphine; Turnquist, Casmir; Horikawa, Izumi; Harris, Brent T.; Harris, Curtis C.
ABSTRACT: Tau accumulation is a core component of Alzheimer's disease and other neurodegenerative tauopathies. While tau's impact on neurons is a major area of research, the effect of extracellular tau on astrocytes is largely unknown. This article summarizes our recent studies showing that astrocyte senescence plays a critical role in neurodegenerative diseases and integrates extracellular tau into the regulatory loop of senescent astrocyte-mediated neurotoxicity. Human astrocytes in vitro undergoing senescence were shown to acquire the inflammatory senescence-associated secretory phenotype (SASP) and toxicity to neurons, which may recapitulate aging- and disease-associated neurodegeneration. Here, we show that human astrocytes exposed to extracellular tau in vitro also undergo cellular senescence and acquire a neurotoxic SASP (e.g. IL-6 secretion), with oxidative stress response (indicated by upregulated NRF2 target genes) and a possible activation of inflammasome (indicated by upregulated ASC and IL-1β). These findings suggest that senescent astrocytes induced by various conditions and insults, including tau exposure, may represent a therapeutic target to inhibit or delay the progression of neurodegenerative diseases. We also discuss the pathological activity of extracellular tau in microglia and astrocytes, the disease relevance and diversity of tau forms, therapeutics targeting senescence in neurodegeneration, and the roles of p53 and its isoforms in astrocyte-mediated neurotoxicity and neuroprotection.